1996
DOI: 10.1038/nm0996-1011
|View full text |Cite
|
Sign up to set email alerts
|

The aging of hematopoietic stem cells

Abstract: We have purified hematopoietic stem cells (HSCs) from the bone marrow of old mice and compared their properties to HSCs in young and middle-aged mice. Single, reconstituting HSCs (by limit dilution) from old and young mice exhibited indistinguishable progenitor activities in vivo. HSCs were five times as frequent in the bone marrow of old mice; however, HSCs from old mice were only one-quarter as efficient at homing to and engrafting the bone marrow of irradiated recipients. HSCs in young and middle-aged mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

61
621
3
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 782 publications
(699 citation statements)
references
References 35 publications
61
621
3
1
Order By: Relevance
“…Competitive repopulation assays in murine transplantation models demonstrated that older bone marrow contains a higher number of repopulating HSC (2-3 fold higher) (Morrison et al, 1996). This is in line with similar in vitro experiments using the cobblestone area forming cell ( …”
Section: Accepted Manuscriptsupporting
confidence: 84%
“…Competitive repopulation assays in murine transplantation models demonstrated that older bone marrow contains a higher number of repopulating HSC (2-3 fold higher) (Morrison et al, 1996). This is in line with similar in vitro experiments using the cobblestone area forming cell ( …”
Section: Accepted Manuscriptsupporting
confidence: 84%
“…Aging of HSCs was thought to be primarily regulated by cell intrinsic‐driven mechanisms (Morrison et al , 1996; Rossi et al , 2005; Chambers & Goodell, 2007; Geiger et al , 2013). In this study, we demonstrate a critical role for decreased OPN in osteoblasts in aged endosteal‐enriched stroma cells for inferring aging‐associated phenotypes on HSCs, while exposing old LT‐HSCs to OPN fragments activated by thrombin results in the attenuation of aging‐associated phenotypes and function of aged HSCs.…”
Section: Discussionmentioning
confidence: 99%
“…HSCs isolated from older mice show defects in mobilization and homing to bone marrow (Morrison et al, 1996;Kim et al, 2003;Liang et al, 2005;Xing et al, 2006). In competitive transplantation assays, a rigorous test for both self-renewal and multipotency during which donor HSCs are co-injected with wild-type bone marrow and assessed for their ability to regenerate all blood lineages, aged HSCs shows defect in long-term reconstitution of the immune system (Sudo et al, 2000;Kamminga et al, 2005;Rossi et al, 2005;Chambers et al, 2007).…”
Section: Defects In Number In Aging Stem Cellsmentioning
confidence: 99%